WRITING A STORY WITH PROVERBS: ANALYSIS OF THE STORY “BOZKURT” BY TÖLÖGÖN KASIMBEKOV - İsmail Turan KALLİMCİ (Fırat University, 2019)
Proverbs are of great importance in terms of reflecting nations’ dominant philosophies and world views and at the same time, they are linguistic materials created to hand down the national heritance to future generations and they make up an important genre of the oral literature. The story, on the other hand, is one of the most effective tools used by authors in the narration of i